Dendritic Spine Plasticity: Function and Mechanisms - Runge, Karen; Cardoso, Carlos; de Chevigny, Antoine (Frontiers in Synaptic Neuroscience, 2020)
Dendritic spines are small protrusions studding neuronal dendrites, first described in 1888 by Ramón y Cajal using his famous Golgi stainings. Around fifty years later the advance of electron microscopy confirmed Cajal's intuition that spines constitute the postsynaptic site of most excitatory synapses in the mammalian brain. The finding that spine density decreases between young and adult ages in fixed tissues suggested that spines are dynamic. It is only a decade ago that two-photon microscopy has unambiguously proven the dynamic nature of spines, through the repeated imaging of single spines in live animals. Spine dynamics comprise formation, disappearance and stabilization of spines and are modulated by neuronal activity and developmental age. Here we review several emerging concepts in the field that start to answer the following key questions: What are the external signals triggering spine dynamics and the molecular mechanisms involved? What is, in return, the role of spine dynamics in circuit rewiring, learning and neuropsychiatric disorders?